Postglacial slip distribution along the Teton normal fault (Wyoming, USA), derived from tectonically offset geomorphological features - Hampel, Andrea; Hetzel, Ralf; Erdmann, Maria-Sophie (Alexandria, Va. : GeoScienceWorld, 2021)
Along the eastern front of the Teton Range, northeastern Basin and Range province (Wyoming, USA), well-preserved fault scarps that formed across moraines, river terraces, and other geomorphological features indicate that multiple earthquakes ruptured the range-bounding Teton normal fault after the Last Glacial Maximum (LGM). Here we use high-resolution digital elevation models derived from lidar data to determine the vertical slip distribution along strike of the Teton fault from 54 topographic profiles across tectonically offset geomorphological features along the entire Teton Range front. We find that offset LGM moraines and glacially striated surfaces show higher vertical displacements than younger fluvial terraces, which formed at valley exits upstream of LGM terminal moraines. Our results reveal that the tectonic offsets preserved in the fault scarps are post-LGM in age and that the postglacial slip distribution along strike of the Teton fault is asymmetric with respect to the Teton Range center, with the maximum vertical displacements (27–23 m) being located north of Jenny Lake and along the southwestern shore of Jackson Lake. As indicated by earlier three-dimensional numerical models, this asymmetric slip distribution results from postglacial unloading of the Teton fault, which experienced loading by the Yellowstone ice cap and valley glaciers in the Teton Range during the last glaciation.